Topical gabapentin 10% in the treatment of epidermolysis bullosa pruritus: A pilot, double‐blind, split‐site, randomized controlled trial. Issue 10 (18th August 2022) - Saki, Nasrin; Vahedi, Samira; Parvizi, Mohammad Mahdi; Shafie'ei, Mohammad; Hosseini, Seyed Ali; Ahramiyanpour, Najmeh
Abstract: Pruritus is a symptom that adversely affects the quality of life of patients with epidermolysis bullosa (EB). Although studies indicate the positive effect of gabapentin on some types of pruritus, its effect on pruritus due to EB remains unexplored. Hence, this study investigated the efficacy of topical gabapentin in treating EB pruritus. We piloted a 6‐week, double‐blind, split‐site, randomized controlled trial on 14 patients with EB pruritus. In each patient, one pruritic lesion received topical gabapentin and the other a placebo. The items of the Leuven Itch Scale were evaluated before and after therapy; the lesions were photographed, and their appearance (i.e., erythema and excoriation severity, pruritic geometric area) was objectively assessed. Statistical analyses were made using SPSS v. 25. Quantitative data were reported as median (interquartile range) or mean ± standard deviation as appropriate. The median age of the 14 patients was 18 years (12–37), and the majority (64.3%) were male. A significant improvement was seen in the geometric area of the pruritic lesion in the intervention group ( p = 0.005) but not in the control group ( p = 0.054). Erythema severity, excoriation intensity, pruritus frequency and duration, and symptom‐related distress significantly improved in both groups ( p < 0.05 in all cases), but topical gabapentin failed to offer any statistical superiority relative to the placebo in the between‐group analysis ( p > 0.05). This study showed no significant difference between topical gabapentin and placebo in erythema severity, excoriation intensity, pruritus frequency and duration, and symptom‐related distress among EB patients. However, the lesion area decreased only in the gabapentin group.